National Dialogue: Innovations for promoting balanced application of macro and micro nutrient fertilizers in Indian agriculture - Cereal Systems Initiative for South Asia (International Food Policy Research Institute, 2019)
The application of fertilizers that do not meet the nutrient requirements (i.e. balanced nutrient application) of target crops is a widespread problem in India. Farmers overuse urea (N) and seldom apply secondary nutrients (Sulphur, Calcium, and Magnesium) and micro-nutrients (like Zinc, Iron, Copper, Boron, Molybdenum and Manganese) in their plots. This imbalanced application of nutrients affects both long-term health of the soil as well as farmers’ own net incomes from agriculture. How do we deploy scientific research, business innovations, and public policies and programs to help promote balanced use of fertilizers in Indian agriculture?